(untitled) (Nuntius Antiquus, 2016)
The paper draws on theoretical work on the representation of the female body as an object of the male gaze in modern narrative, in order to decode and analyze Helen’s portrayal as a physical vacuum in ancient literature. I argue that the negation of Helen’s corporeality emphasizes the semiotic duality of her body, allowing it to be deployed both as a sign and as a site for the inscription of signs. The paper, then, proceeds to show how Helen’s Iliadic depiction has provided the eighteenth-century philosopher Edmund Burke with a rhetorical platform upon which to theorize the aesthetic dichotomy between the beautiful and the sublime. I close my analysis by illustrating how the eclecticism, compromises, and pastiches that inform Helen’s cinematic recreations find a parallel in, and thus perpetuate, ancient pictorial techniques.